A multicenter phase II trial to determine the safety and efficacy of combination therapy with denileukin diftitox and cyclophosphamide, doxorubicin, vincristine and prednisone in untreated peripheral T-cell lymphoma: the CONCEPT study. Issue 7 (1st July 2013) - Foss, Francine M.; Sjak-Shie, Nelida; Goy, Andre; Jacobsen, Eric; Advani, Ranjana; Smith, Mitchell R.; Komrokji, Rami; Pendergrass, Kelly; Bolejack, Vanessa
Abstract: This phase II study to determine the safety and efficacy of denileukin diftitox (DD) and cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) enrolled patients with newly diagnosed peripheral T-cell lymphoma (PTCL). Forty-nine received DD 18 μg/kg/day (days 1, 2) with CHOP (day 3) every 21 days for ≤ 6–8 cycles. Intent-to-treat (ITT) and safety populations comprised all patients. In the ITT population, the overall response rate was 65%, median duration of response was 30 months and median progression-free survival was 12 months. Median overall survival was not attained at the end of the study, and the overall survival rate was 63.3%. The two most frequent treatment-related adverse events (AEs) were fatigue and nausea. Most frequent AEs ≥ grade 3 within the hematologic system were lymphopenia (24.5%), neutropenia (20.4%) and leukopenia (18.4%). Three treatment-related deaths occurred. DD plus CHOP was well tolerated, and progression-free and overall survival improved versus historical comparison with CHOP alone. Confirmation in larger trials is warranted.